Multilayer End Coupled Band Pass Filter using Low-Temperature Co-Fired Ceramic Technology for Broadband Fixed Wireless - Zulkifli Ambak; Hizamel M. Hizan; Ahmad Ismat Abdul Rahim; Azmi Ibrahim; Mohd Zulfadli M. Yusoff; Razali Ngah (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
This paper presents design approach for realizing multilayer End Coupled Bandpass Filter (ECBPF) using low temperature co-fired ceramic (LTCC) technology at TMRND's LTCC Lab. Design method for the ECBPF is based on the coupled-resonator filter which was realized in LTCC multilayer substrate and operating at the center frequency of 42GHz. Three samples of EC BPF have been designed, simulated, fabricated and investigated in terms of performance and structure size.This multilayer ECBPF were fabricated in the 8 layers LTCC Ferro A6S materials with dielectric constant of 5.8, loss tangent of 0.002 and metallization of gold. The measured insertion loss for ECBPF was 2.43dB and return loss was 22.81dB at the center frequency at 42GHz. The overall size of the fabricated filter was 6.0 mm x 2.5 mm x 0.77 mm.